PIRATES OF AFRICA’S SOMALI COAST: ON TERRORISM’S BRINK? - Swart, Gerrie (Scientia Militaria - South African Journal of Military Studies, 2011)
This article will examine and evaluate the potential threat of maritime terrorism in Africa, in particular the threat posed at present off the Somali coast. Africa’s porous borders have provided an ideal conduit for the export of terrorism on land, and now its unguarded coastlines are a potential new thoroughfare for maritime terrorists to operate at sea. In Africa, the threat to maritime security and the proliferating threat of ungoverned spaces have lethally combined to spawn the major threat of piracy and now also the potential threat of maritime terrorism off the insecure coastline of Somalia. At the time of writing, the security threats and challenges posed by the rapid proliferation of piracy remains, and have continued to be so throughout 2009. As of recent, maritime experts observe that the waters off the coast of Somalia and the Gulf of Aden have emerged as the most dangerous zones for seafarers.